AWARENESS OF NUTRITIONAL ANEMIA AMONG FEMALE PATIENTS AGED 18 - 49 YEARS AT CAM LE DISTRICT HEALTH CENTER, DA NANG CITY IN 2022 - Nguye Thi, Hai Lam; Nguye Thi, Thuy Le; Tran Van, Thom; Luong Thi, Lan (TẠP CHÍ PHÒNG CHỐNG BỆNH SỐT RÉT VÀ CÁC BỆNH KÝ SINH TRÙNG, 2024)
A cross-sectional descriptive study was conducted among 175 female patients aged 18-49 years old examined at Cam Le district health center, Danang city from February 2022 to September 2022 to describe the awareness and some related factors in the prevention of nutritional anemia. Results showed that 98.9% of the patients were aware of the cause of nutritional anemia that is due to iron deficiency; 86.9% knew that worm infection can cause anemia; 99,4% knew that signs and symptoms of anemia are pale skin; 98.3% understood those symptoms including headache, dizziness, fainting; 97.1% knew that the symptom of anemia is fatigue; 96.9% were aware that anemia can cause abortion, preterm labor, haemorrhage; 89.7% knew that anemia can cause memory loss; 86.3% knew anemia can lead to work impairment; 96% understood that the risk group includes pregnant women, breastfeeding women; 73.7% knew that the risk group consists women of reproductive age; 73.7% had good general knowledge of nutritional anemia. Some other related factors included age, academic level, home economics and marital status (p<0,05). Knowledge about nutritional anemia of women aged 18-49 years was quite good. It is necessary to maintain the communication and health education about anemia and the prevention of nutritional anemia so that research subjects can better apply this practice. Key words: awareness, nutritional anemia, women of reproductive age